WYNAGRODZENIE DOZORCY RZECZY RUCHOMYCH W POSTĘPOWANIU EGZEKUCYJNYM - Jędrejek, Grzegorz (Zeszyty Prawnicze, 2016)
THE CARETAKER’S FEE FOR THE CUSTODY OF MOVABLES IN FORECLOSURE Summary In compliance with the relevant Polish provisions, movables impounded by a bailiff are to be left in the custody of the person with whom they were found. In Article 855 of the Polish Code of Civil Procedure the legislator recognises the bailiff’s option to put impounded movables in the custody of another person, includinga creditor, who then performs the duties of caretaker of the impoundedmovables. The aim of this article is to present issues related to thecaretaker’s fee in foreclosure proceedings. When a movable item isentrusted to the custody of a third party a regulatory relation in publiclaw arises between the bailiff and the caretaker. The caretaker’s fee ispart of the costs of repossession, and are payable in the foreclosureproceedings. The costs of repossession, including the caretaker’s fee, may not be claimed in separate proceedings.